Exploring Medical Expert Testimony and its Contribution to Miscarriages of Justice An Examination of the Flawed Pathological Evidence of Dr Charles Smith - Thom, Ashley C (University of Ottawa (Canada), 2010)
Wrongful convictions have garnered recent increased attention in Canada, but specific concern with the use of medical expert evidence in criminal trials is especially timely. With the recent Inquiry into Pediatric Forensic Pathology in Ontario, it has become clear that flawed medical expert evidence can have devastating effects on individuals and criminal trials. The theoretical framework of social constructionism was used in a cross-case pattern analysis to provide a foundation for examining the problematic expert testimony of Dr. Charles Smith in eight cases of unexplained child death. The findings suggest that Dr. Smith's expert evidence was not adequately evaluated at the gate of admissibility, and may have been evaluated by internalized judgments rather than direct assessments of that evidence. The results indicate a combination of contributing factors of Dr. Smith's flawed expert evidence and the subsequent miscarriages of justice, as Dr. Smith's flaws were overlooked and his testimony accepted uncritically.
Keywords: Law.; Sociology, Criminology and Penology.